Development of a Swedish short version of the Montreal Cognitive Assessment for cognitive screening in patients with stroke - Tamar Abzhandadze; Erik Lundström; Dongni Buvarp; Marie Eriksson; Terence J. Quinn; Katharina S. Sunnerhagen (Medical Journals Sweden, 2023)
Objective: The primary objective was to develop a Swedish short version of the Montreal Cognitive Assessment (s-MoCA-SWE) for use  with patients with stroke. Secondary objectives were to identify an optimal cut-off value for the s-MoCA-SWE to screen for cognitive impairment and to compare its sensitivity with that of previously developed short forms of the Montreal Cognitive Assessment. Design: Cross-sectional study. Subjects/patients: Patients admitted to stroke and rehabilitation units in hospitals across Sweden. Methods: Cognition was screened using the Montreal Cognitive Assessment. Working versions of the s-MoCA-SWE were developed using supervised and unsupervised algorithms. Results: Data from 3,276 patients were analysed (40% female, mean age 71.5 years, 56% minor stroke at admission). The suggested s-MoCA-SWE comprised delayed recall, visuospatial/executive function, serial 7, fluency, and abstraction. The aggregated scores ranged from 0 to 16. A threshold for impaired cognition ≤ 12 had a sensitivity of 97.41 (95% confidence interval, 96.64-98.03) and positive predictive value of 90.30 (95% confidence interval 89.23-91.27). The s-MoCA-SWE had a higher absolute sensitivity than that of other short forms. Conclusion: The s-MoCA-SWE (threshold ≤ 12) can detect post-stroke cognitive issues. The high sensitivity makes it a potentially useful "rule-out" tool that may eliminate severe cognitive impairment in people with stoke. LAY ABSTRACT Stroke survivors have an increased risk of developing cognitive impairment, a common consequence of stroke. Therefore, many international guidelines recommend cognitive screening for all patients admitted to hospital with stroke. The Montreal Cognitive Assessment (MoCA) has been recommended as an appropriate cognitive test to be applied in stroke units. Although the administration of MoCA takes approximately 15 min, the screening can take longer in patients with acute stroke. Therefore, this study aimed to develop a Swedish short version of the Montreal Cognitive Assessment (s-MoCA-SWE) based on data from a large Swedish sample of acute and early subacute stroke survivors. The current study analysed data from 3,276 patients and suggest an s-MoCA-SWE that comprised the following tasks: delayed recall, visuospatial/executive function, serial 7, fluency, and abstraction. The s-MoCA-SWE could identify cognitive impairment in 97% of patients. In conclusion, s-MoCA-SWE has the potential to rule out severe cognitive impairment.